Huanshaodan regulates microglial glucose metabolism reprogramming to alleviate neuroinflammation in AD mice through mTOR/HIF-1α signaling pathway - Shang, Congcong; Su, Yunfang; Ma, Jinlian; Li, Zhonghua; Wang, Pan; Ma, Huifen; Song, Junying; Zhang, Zhenqiang (Frontiers in Pharmacology, 2024)
Abnormal glucose metabolism in microglial is closely associated with Alzheimer's disease (AD). Reprogramming of microglial glucose metabolism is centered on regulating the way in which microglial metabolize glucose to alter microglial function. Therefore, reprogramming microglial glucose metabolism is considered as a therapeutic strategy for AD. Huanshaodan (HSD) is a Chinese herbal compound which shows significant efficacy in treating AD, however, the precise mechanism by which HSD treats AD remains unclear. This study is aim to investigate whether HSD exerts anti-AD effects by regulating the metabolic reprogramming of microglial through the mTOR/HIF-1α signaling pathway. SAMP8 mice and BV2 cells were used to explore the alleviative effect of HSD on AD and the molecular mechanism in vivo and in vitro. The pharmacodynamic effects of HSD was evaluated by behavioral tests. The pathological deposition of Aβ in brain of mice was detected by immunohistochemistry. ELISA method was used to measure the activity of HK2 and the expression of PKM2, IL-6 and TNF-α in hippocampus and cortex tissues of mice. Meanwhile, proteins levels of p-mTOR, mTOR, HIF-1α, CD86, Arg1 and IL-1β were detected by Western-blot. LPS-induced BV2 cells were treated with HSD-containing serum. The analysis of the expression profiles of the CD86 and CD206 markers by flow cytometry allows us to distinguish the BV2 polarization. Glucose, lactic acid, ATP, IL-6 and TNF-α levels, as well as lactate dehydrogenase and pyruvate dehydrogenase activities were evaluated in the BV2. Western-blot analysis was employed to detect mTOR, p-mTOR, HIF-1α and IL-1β levels in BV2. And the mTOR agonist MHY1485 (MHY) was chosen to reverse validate. In this study, it is found that HSD improved cognitive impairment in SAMP8 mice and reduced Aβ deposition, suppressed the levels of glycolysis and neuroinflammation in mice. In LPS-induced BV2 cells, HSD also regulated glycolysis and neuroinflammation, and suppressed the mTOR/HIF-1α signaling pathway. More importantly, these effects were reversed by MHY. It is demonstrated that HSD regulated microglial glucose metabolism reprogramming by inhibiting the mTOR/HIF-1α signaling pathway, alleviated neuroinflammation, and exerted anti-AD effects. This study provided scientific evidence for the clinical application of HSD for treating AD.